PENETRATION TESTING MENGGUNAKAN OWASP TOP 10 PADA DOMAIN XYZ.AC.ID - Alexander Dharmawan (Electro Luceat, 2022)
With the increasing number of internet service users, more and more information can be obtained from the internet. Information itself is important in this digital era for organizations, businesses and individuals. More and more individuals provide information about them on the internet, making their privacy less and more recently, many individuals are starting to become aware of how the information they provide is used and more and more organizations are starting to pay attention to information security risks that can have a negative impact and material loss on the process. business, image of the organization, customer trust and affect relationships with customers or their business partners. In an effort to maintain data and information security, there is a method called penetration testing. Penetration testing is a series of methods used to test the security of a system. The penetration testing process involves an analysis of a system to look for potential security vulnerabilities such as system configuration errors, defects in software and hardware development and weaknesses in the logic of a process.